Validation of predictive equation for height using demi-span among Universiti Sultan Zainal Abidin staff - Sakinah, Harith; Lucy, Juhanis (2020)
Demi-span measurement is a method used to estimate height of an individual, especially for those whose height cannot be directly measured. Height is a crucial parameter that is needed to determine other parameters that help in the assessment of one’s nutritional status, such as body mass index (BMI). Therefore, this study was conducted to validate the equation for demi-span measurement proposed by Ngoh et al. (2012). This cross-sectional study involved 118 employees of Universiti Sultan Zainal Abidin (UniSZA), Kuala Nerus, Terengganu, Malaysia, who were in the age group of 30-55 years. Weight, height, and demi-span were measured using the standard procedures. The results showed that adult anthropometrics differed on the basis of gender (p < 0.001) and age (p < 0.05). The height calculated from the equations and the measured height showed consistent agreement and similarity (r = 0.944 and r = 0.949, respectively). The calculated height led to a BMI estimate that was close to the actual BMI (r = 0.997 and r = 0.996, respectively) calculated from the measured height. In conclusion, the demi-span equation showed good reliability and was suitable to estimate height and BMI of adult individuals in Malaysia.